A Call to APSA Part 2: Bring in Community College Faculty. Issue 1 (1st January 2022) - Osorio, Maricruz Ariana; Parker, Sara; Richards, Erin
ABSTRACT: This article uses data from a 2018 survey conducted by the American Political Science Association Committee on the Status of Community Colleges in the Profession to make specific policy recommendations for how to better reach out to and incorporate political science faculty teaching at community colleges into the association.